Radion tunneling in modified theories of gravity - Tanmoy Paul (European Physical Journal C: Particles and Fields, 2018)
Abstract We consider a five dimensional warped spacetime where the bulk geometry is governed by higher curvature F(R) gravity. In this model, we determine the modulus potential originating from the scalar degree of freedom of higher curvature gravity. In the presence of this potential, we investigate the possibility of modulus (radion) tunneling leading to an instability in the brane configuration. Our results reveal that the parametric regions where the tunneling probability is highly suppressed, corresponds to the parametric values required to resolve the gauge hierarchy problem.